ANALISA YURIDIS TERHADAP EKSEKUSI PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA YANG TELAH BERKEKUATAN HUKUM TETAP ATAS OBJEK SENGKETA YANG SAMA DENGAN PUTUSAN YANG BERBEDA: (Studi Kasus Perkara No. 145/Pdt.G/1998/PN. Smg&Perkara No. 14/Pdt.G/2005/PN. Smg) - Manab, Abd; Rahman, Taufikur (ASA, 2022)
Humans in social interactions in the life of society, nation and state, often cause conflict between one another. This conflict can sometimes be resolved peacefully, sometimes it also causes continuous tensions, causing disputes on both sides. Based on the description of the Juridical Review of the Execution of Decisions of the Supreme Court of the Republic of Indonesia which have permanent legal force on the same object of dispute with different decisions (Case Study of Decision on Case No. 145/ Pdt.G/1998/ PN. SMG and Decision on Case No. 14 / Pdt.G/ 2005/ PN. SMG), it can be concluded as follows: That the implementation of the decision or execution of 2 (two) decisions of the Supreme Court of the Republic of Indonesia which have permanent legal force on the object of the same dispute is in accordance with the laws and regulations. The applicable invitation is the provisions of the Civil Procedure Code (HIR), that the right solution to ensure legal certainty for justice seekers through the Judiciary is to request a judicial review.